2023
DOI: 10.1037/adb0000892
|View full text |Cite
|
Sign up to set email alerts
|

Nudges and choice architecture to promote healthy food purchases in adults: A systematized review.

Abstract: Objective: Consistent with behavioral economic models that emphasize the context-dependance of behavioral choice, choice architecture strategies change the environmental context to promote or nudge healthier choices including the healthfulness of food purchases that may help reduce disease and premature death. This review summarizes research that investigated nudging interventions to promote healthful food purchase choices among adults. Method: A comprehensive systematized search strategy identified research p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…15 There are several examples in the RFE literature of these strategies being predominantly used to sell less healthy products 16 with current evidence showing promise for altering these RFE attributes to improve consumer purchasing practices to better align with dietary guidelines. 17 As one example, Winker et al (2022) found men to be particularly responsive to marketing for sugary drinks in smaller store/convenience settings (akin to truck stop RFEs) in comparison to women. 18 Given the overwhelming number of truck drivers who are men, limiting such unhealthful marketing may be especially impactful.…”
Section: Moving Upstream To Improve Truck Driver Nutrition By Address...mentioning
confidence: 99%
“…15 There are several examples in the RFE literature of these strategies being predominantly used to sell less healthy products 16 with current evidence showing promise for altering these RFE attributes to improve consumer purchasing practices to better align with dietary guidelines. 17 As one example, Winker et al (2022) found men to be particularly responsive to marketing for sugary drinks in smaller store/convenience settings (akin to truck stop RFEs) in comparison to women. 18 Given the overwhelming number of truck drivers who are men, limiting such unhealthful marketing may be especially impactful.…”
Section: Moving Upstream To Improve Truck Driver Nutrition By Address...mentioning
confidence: 99%
“…Applying principles of choice architecture to design environments to nudge consumers towards healthier options may improve the success of setting-based healthy eating interventions in RSS. Choice architecture has been studied in a variety of settings, including food retailers ( Kraak et al , 2017 ; Houghtaling et al , 2019 ; Lindstrom et al , 2022 ), workplaces ( Al-Khudairy et al , 2019 ; Rantala et al , 2021 ), schools ( Skov et al , 2013 ; Nørnberg et al , 2016 ) and health care settings ( Al-Khudairy et al , 2019 ), however, it has not been comprehensively reviewed in RSS.…”
Section: Introductionmentioning
confidence: 99%
“…These published systematic reviews cover a wide range of behaviors. These include healthy food choices 25,[29][30][31][32][33][34][35][36][37][38][39] , dietary behaviors [40][41][42][43][44] , other health related behaviors 36,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] , environmental behaviors [61][62][63][64][65][66][67] , disclosure of personal information 68 , tax compliance 69 , learning behavior 70 and children's sleep 71 . Additionally, some of the reviews address various types of interventions such as digital nudges 72 or default options 73 .…”
Section: The Case Of Inflated Effect Sizesmentioning
confidence: 99%